Inside Cover: Reducing the Cost and Preserving the Reactivity in Noble‐Metal‐Based Catalysts: Oxidation of CO by Pt and Al–Pt Alloy Clusters Supported on Graphene (Chem. Eur. J. 15/2016). Issue 15 (26th February 2016) - Koizumi, Kenichi; Nobusada, Katsuyuki; Boero, Mauro
Abstract : Reactive dynamical simulations elucidate the catalytic oxidation of CO to CO2 on graphene‐supported Pt and Pt–Al alloy clusters. The general mechanism evidenced is a Langmuir–Hinshelwood pathway. The graphene support transfers electrons to the clusters, which, in turn, promotes a subsequent charge transfer from the clusters to the adsorbed O2 molecule. This O2 molecule dissociates on the cluster surface and the atomic O reacts with an approaching CO producing CO2 . Moreover, Al doping in a pure Pt cluster is shown to be a viable way to reduce costs without hindering the catalytic activity. More information can be found in the Full Paper by K. Nobusada et al. onpage 5181 ff.